Fabrication of microfluidic chip mold based on through-mask electrochemical etching and micro electroforming process. (3rd May 2018) - Du, Liqun; Zhao, Wenjun; Zhai, Ke; Song, Chang; Li, Qingfeng
Abstract: During the fabrication of nickel microfluidic chip mold insert, the problem of poor interfacial adhesion strength between electroformed layer and substrate often appeared which seriously reduced the service lifetime of the micro mold. In this paper, a novel pretreatment method of pickling and through-mask electrochemical etching was proposed to improve the interfacial adhesion strength of nickel microfluidic chip molds. Micro beams were used for exploring the effect of different pretreatment parameters on improving the adhesion strength. The adhesion strength was measured through a micro shearing test. The test results show that the mean interfacial adhesion strength without pretreatment is 52.1 MPa, and the interfacial adhesion strengths of other three groups with different pretreatment parameters are 103.4 MPa, 158.2 MPa and 229.7 MPa, respectively. The result indicated that pickling and electrochemical etching can effectively improve the adhesion strength between electroformed layer and substrate. Besides, in order to find the most suitable fabrication parameters for nickel mold insert, lateral corrosion, etching depth and etching surface area were also analyzed. The measured results show that the adhesion strength almost increases linearly with the increase of etching surface area in a scope of 1.50 mm 2 to 2.07 mm 2 . Overall consideration, when a double cross-shaped microfluidic chip mold insert was fabricated by pretreatment of pickling for 20 s and electrochemical etching for 5 min, the micro mold insert has higher interfacial adhesion strength and the substrate has a moderate lateral corrosion, which contributes to extending the service life of microfluidic chip mold.